Motivations and Land-Use Intentions of Nonindustrial Private Forest Landowners: Comparing Inheritors to Noninheritors - Indrajit Majumdar; David Laband; Lawrence Teeter; Brett Butler (Forest Science, 2009)
The documented importance of intergenerational human capital transfers in agriculture generally gives us reason to suspect that such transfers may be important in a forestry context and that there may be important implied differences between first-generation woodland owners and multigeneration woodland owners with respect to their motivations and future intentions. In turn, knowledge of the motivations and intentions of nonindustrial private landowners may be extremely important because such knowledge may be vital in terms of our ability to predict future timber supply and the availability of nontimber amenities. Also, the effectiveness of public policies targeting nonindustrial private forest landowners may depend critically on their motivations and intentions. In this article, we analyzed 8,373 responses to the National Woodland Owner Survey to compare characteristics, motivations, and intentions of multigeneration forest landowners against those of single-generation forest landowners. In brief, we found there were significant differences in their motivations and management behavior; inheritors are more active forest managers and manage for both timber and nontimber forest products more aggressively than noninheritors who typically value esthetics, privacy, protection of biodiversity, and nonhunting recreation.

Factors that Influence Administrative Appeals of Proposed USDA Forest Service Fuels Reduction Actions - David N. Laband; Armando González-Cabán; Anwar Hussain (Forest Science, 2006)
Using the database developed by the General Accounting Office on proposed fuels reduction actions on federal lands in 2001 and 2002, we conduct probit regression analysis to identify factors that significantly affect the likelihood of administrative appeal. The likelihood of appeal of a proposed fuels reduction action is significantly increased by (1) the size of area affected, (2) the number of proposed activities at the site, (3) when one of the stated purposes is commodity production (timber and sawlogs), (4) when one of the stated purposes is reduction of project-generated fuels, (5) implementation involves prescribed burning or mechanical thinning, and (6) the presence of at least one species of mammal at risk of extinction in the immediate vicinity of the site. Conversely, the likelihood of appeal is significantly reduced if (7) implementation is handled by Forest Service personnel or using a service contract, and (8) the proposed action is located in a Wildland–Urban Interface area. However, we also observe persistent regional effects, with fuels reduction proposals in Region 1 (3, 6, 8) characterized by a significantly higher (lower) likelihood of appeal than proposals in the other regions.